2017
DOI: 10.1148/radiol.2017162352
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Strangulation in Adhesive Small Bowel Obstruction on the Basis of Combined CT Findings: Implications for Clinical Care

Abstract: Purpose To determine which computed tomography (CT) findings or combinations of findings can help to accurately identify strangulation in adhesive small bowel obstruction (SBO). Materials and Methods Contrast agent-enhanced CT findings in a cohort of 256 patients consecutively admitted for adhesive SBO, with a delay of less than 24 hours between CT and surgery for the operated patients, were reviewed independently by two radiologists, with consensus by a third, to assess CT findings commonly associated with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 31 publications
2
56
0
1
Order By: Relevance
“…reported that reduced the bowel enhancement, diffused mesenteric haziness, and closed-loop mechanism of obstruction were important and associated with strangulation. When two or three of the above-mentioned CT findings were present, the high values related to the likelihood ratio of strangulation were 14.7 and 43.8, respectively [25]. In our case, multiple adhesion bands were detected and there was no evidence of strangulation and ischemia.…”
Section: Discussionsupporting
confidence: 43%
“…reported that reduced the bowel enhancement, diffused mesenteric haziness, and closed-loop mechanism of obstruction were important and associated with strangulation. When two or three of the above-mentioned CT findings were present, the high values related to the likelihood ratio of strangulation were 14.7 and 43.8, respectively [25]. In our case, multiple adhesion bands were detected and there was no evidence of strangulation and ischemia.…”
Section: Discussionsupporting
confidence: 43%
“…A variety of CT signs, such as mesenteric uid, mesenteric venous congestion free peritoneal uid, and reduced bowel enhancement, have been reported as ndings related to bowel strangulation [15][16][17][18]. Millet et al reported that a reduced enhancement of the bowel wall is highly predictive of ischemia [15].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies [13][14][15] have investigated the usefulness of CT findings for predicting bowel necrosis.…”
Section: Discussionmentioning
confidence: 99%